An Investigation of EFL Preservice Teachers’ Attitudes and Motivations in Developing a Digital Learning Video - Tri Wintolo Apoko; Silih Warni (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This research is aimed at investigating EFL preservice teacher’s attitudes and motivations in developing a digital learning video and the difficulties found in developing a digital learning video. The research was conducted at University of Muhammadiyah Prof. Dr. Hamka. There are 67 EFL preservice teachers who became the participants taken by purposive sampling technique. A mixed method was used. The questionnaire was distributed to all participants to respond to their attitudes and motivations, and nine participants were invited to have an individual interview. A descriptive statistic was used to analyze the questionnaire data and a description and image analysis was utilized to analyze the open-ended questions and the interview data. The results show that (1) the EFL preservice teachers’ attitudes in developing a digital learning video are in the higher level as the mean of their responses from four items ranging between 3.16 to 3.21, (2) the EFL preservice teachers’ motivations in developing a digital learning video are also in the higher level in which the mean of their responses ranged from 3.12 to 3.36, and (3) the difficulties faced in developing a digital learning video include: skills of using applications, providing materials, software capability, confidence, and time availability. Therefore, the implications cover the learning video quality produced by EFL preservice teachers to attract students’ attention to learn English better, the variety of video editing applications used in overcoming students’ learning boredom, and encouraging EFL preservice teachers to continue learning and practicing to create and edit the videos better.